Physics Teachers’ Ability in Planning and Implementing Cultural-Based Physics Learning Activities on Education and Training - Soko, Imelda Paulina; Setiawan, Agus; Widodo, Ari (Jurnal Penelitian dan Pembelajaran IPA, 2019)
There is increasing appreciation of the importance of using indigenous (traditional) knowledge for contextualizing school science instruction because it forms part of students’ prior experiences and source of information that they carry to school learning. The purpose of this study is to describe the physics teachers’ ability in planning and implementing cultural-based physics learning activities, and the relationship between the teachers’ ability in planning and implementing cultural-based physics learning. The research was a quantitative descriptive study that included 20 physics teachers in one of the regencies of Nusa Tenggara Timur (NTT) as the subject of the study. The instruments used for this study were the assessment rubrics for the physics lesson plan and peer teaching. The data were collected by doing observation and documentation of participatory education and training activities with cultural approach, analysed descriptively quantitatively, and presented in categories, percentages and diagrams. The average ability of physics teachers in designing the lesson plans of cultural-based physics in the following categories was quite good: 17 teachers (85%) were in the good category while 3 teachers (15%) were in very good category. The average presentation of the peer teaching appraisal results was in fairly good category, only 1 teacher (5%) was in the less good category, then 14 teachers (70%) were in good enough category, and then 4 teachers (25%) were in good categories. In general, the physics teachers had presented good performances, which mean the training activities had a positive effect on the physics teachers’ content and pedagogical knowledge. In education and training activities by integrating culture in physics learning activities responded very well, thus in every group discussion cycle, the teacher was able to identify the culture which was suitable to the content of existing material and implementing it in the peer teaching activities.